Regulating Digital Marketplaces: A Comparative Socio-Legal Analysis of Consumer Protection in Islamic and Western Legal Traditions - Toheed Ahmad (INDONESIAN JOURNAL OF SUSTAINABILITY, 2026)
The rapid advancement of digital technologies has fundamentally transformed global commerce, leading to the emergence of digital marketplaces and platform-based economies that facilitate cross-border electronic transactions. While e-commerce platforms have expanded economic opportunities and improved consumer access to goods and services, they have simultaneously generated significant legal and regulatory challenges concerning consumer protection, contractual fairness, data privacy, and dispute resolution. Consumers participating in online transactions frequently encounter risks associated with misleading advertising, unfair contractual terms, cyber fraud, misuse of personal data, and jurisdictional complexities in resolving transnational disputes. In response, legal systems across the world have developed regulatory frameworks aimed at safeguarding consumer rights and ensuring transparency and accountability in digital commerce.This study examines the regulation of digital marketplaces through a comparative socio-legal analysis of e-commerce governance in Islamic and Western legal systems. Employing a qualitative doctrinal and comparative legal methodology, the research analyzes the legal principles governing electronic commerce, consumer protection standards, and dispute resolution mechanisms within both traditions. The study further explores the ethical foundations of Islamic commercial jurisprudence, including the principles of fairness (adl), transparency, good faith, and mutual consent, and compares them with statutory and institutional consumer protection frameworks developed in Western legal systems. In addition, the research investigates the socio-legal dimensions of digital commerce, particularly the influence of cultural values, institutional structures, technological innovation, and regulatory enforcement on consumer protection practices.The findings demonstrate that both Islamic and Western legal systems share common objectives in promoting fairness, preventing exploitation, and protecting consumers from deceptive commercial practices, although they differ in their legal methodologies and regulatory approaches. Western legal systems predominantly rely on comprehensive legislation, administrative regulation, and consumer protection agencies, whereas Islamic legal systems integrate ethical-commercial principles with legal norms to regulate market conduct. Despite these methodological differences, both frameworks emphasize transparency, accountability, contractual justice, and the protection of weaker parties in commercial transactions.The study concludes that effective governance of digital marketplaces requires enhanced legal harmonization and international cooperation to address the cross-border complexities of global e-commerce. Strengthening transparency obligations, improving online dispute resolution mechanisms, ensuring data protection, and promoting responsible platform governance are essential for enhancing consumer confidence in digital markets. The integration of ethical principles derived from diverse legal traditions may further contribute to the development of more inclusive, balanced, and sustainable regulatory frameworks capable of supporting the continued growth of the global digital economy while safeguarding consumer rights and commercial justice.Keywords: Digital Marketplaces; Consumer Protection; E-Commerce Regulation; Islamic Commercial Law; Comparative Legal Analysis